Update Magnetic Field Sensors Could Help Halt Runway Crashes. - Dumiak, M.
Air-traffic control is a complex and high-stress business. Mistakes are not allowed. And it's not limited to directing planes for takeoff and landing - a job that's been memorably described as three-dimensional chess. It also includes keeping track of where planes are on the ground. According to safety watchdog Eurocontrol, in 2005 alone there were 600 occasions when people, cars, or planes crossed Europe's airport taxiways when they shouldn't have. In fact, the most deadly airline accident ever happened on the ground: in 1977, two 747 jumbo jets collided in the Canary Islands, killing 583 people. Most big airports have expensive ground-radar systems to keep track of where the hundreds of moving planes are on the sprawling tarmacs. But ground radar sometimes reflects off buildings and terminals, leaving small gaps in coverage. Smaller airports like the one in Thessaloniki, Greece, can't afford ground radar. Such blind spots on the ground at airports large and small have prompted European researchers to explore the use of fluctuations in the Earth's magnetic field to better pinpoint where planes are on busy taxiways. The results, researchers say, show that using US 150 sensors can fill in the blind spots.
Keywords: Earth magnetic field fluctuation; Eurocontrol; Air-traffic control; Airplane tracking; Ground-radar systems; Magnetic field sensors; Runway crash prevention; Taxiways